The rage of innocence : how America criminalizes Black youth - Henning, Kristin, (Law teacher) (Pantheon Books, 2021)
"Drawing upon 25 years of experience representing black youth in Washington D.C.'s juvenile court, Kris Henning confronts America's irrational, manufactured fears of Black youth and makes a powerfully compelling case that the crisis in racist American policing begins with its relationship to Black children. She explains how discriminatory and aggressive policing has socialized a generation of Black teenagers to fear, resent, and resist the police, and details the long-term consequences of racism and trauma Black youth experience at the hands of police and their vigilante surrogates. She makes clear that unlike white youth who are afforded the freedom to test boundaries, experiment with sex and drugs, and figure out who they are and want to be, Black youth are seen as a threat to white America and are denied healthy adolescent development. She examines the criminalization of Black adolescent play and sexuality, and of Black fashion, hair and music. She limns the effects of police presence in schools, and the depth of policing-induced trauma in Black adolescents. Especially in the wake of the recent unprecedented, worldwide outrage at racial injustice and inequality, The Rage of Innocence: How America Criminalizes Black Youth is an essential book for our moment"--